Answer:
False
Step-by-step explanation:
This transformation is a rotation. If it were a reflection the moon shape would be at a 180 degree flip but instead is at a 90 degree rotation.
Hope this helped!
Answer:
v = - 3
Step-by-step explanation:
Given
v = u + at ← substitute u = 2, a = - 5, t = 1 into the expression
v = 2 + (- 5 × 1) = 2 + (- 5) = 2 - 5 = - 3
Answer:
![\sum^\infty_{n=0} -5 (\frac{x+2}{2})^n](https://tex.z-dn.net/?f=%5Csum%5E%5Cinfty_%7Bn%3D0%7D%20-5%20%28%5Cfrac%7Bx%2B2%7D%7B2%7D%29%5En)
Step-by-step explanation:
Rn(x) →0
f(x) = 10/x
a = -2
Taylor series for the function <em>f </em>at the number a is:
![f(x) = \sum^\infty_{n=0} \frac{f^{(n)}(a)}{n!} (x - a)^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Csum%5E%5Cinfty_%7Bn%3D0%7D%20%5Cfrac%7Bf%5E%7B%28n%29%7D%28a%29%7D%7Bn%21%7D%20%28x%20-%20a%29%5En)
............ equation (1)
Now we will find the function <em>f </em> and all derivatives of the function <em>f</em> at a = -2
f(x) = 10/x f(-2) = 10/-2
f'(x) = -10/x² f'(-2) = -10/(-2)²
f"(x) = -10.2/x³ f"(-2) = -10.2/(-2)³
f"'(x) = -10.2.3/x⁴ f'"(-2) = -10.2.3/(-2)⁴
f""(x) = -10.2.3.4/x⁵ f""(-2) = -10.2.3.4/(-2)⁵
∴ The Taylor series for the function <em>f</em> at a = -4 means that we substitute the value of each function into equation (1)
So, we get
Or ![\sum^\infty_{n=0} -5 (\frac{x+2}{2})^n](https://tex.z-dn.net/?f=%5Csum%5E%5Cinfty_%7Bn%3D0%7D%20-5%20%28%5Cfrac%7Bx%2B2%7D%7B2%7D%29%5En)
225998 225988
I believe it is the tenths place
(the bold digits)
Answer:
f(-2) = -4x + 6
Step-by-step explanation:
f(x) = 2x + 6
f(-2) = -2(2x) + 6
f(-2) = -4x + 6